Development of Teaching Material Supplement for Geography Subject Based on Local Wisdom of Kaili Da'a in Sigi Regency, Central Sulawesi - Abdul Latief, Juraid; Listiqowati, Ika; Abd Muis, Arifuddin (CV. Inara, 2021)
The aim of the research was to develop a supplement of teaching materials for classXI geography subjects based on the local wisdom of the Kaili Da'a tribe in SigiRegency, Central Sulawesi, which is valid and feasible. Before developing thesupplement of teaching materials, first make preparations, namely: (1) Kaili Da'aresearch community in Dombu village, Marawola Sub district, Sigi Regency relatedto local wisdom values that are relevant to the geography material of XI high schoolclass. (2) Examines the Content Competency, Basic Competence, Teaching Materialand values of local wisdom that can be implemented in the geography learningmaterials of class XI high school. Teaching material supplements developed werevalidated by material experts and linguists. Products validated by material expertsand linguists show a percentage of 85% with qualifications that are very suitable foruse, after which a revision is made. The revised teaching material supplement wasthen tested for eligibility in small groups. The small group was 20 students of SMA 4Sigi, 20 students of SMA AL-Khairat Kalukubula, and 20 students of SMA 2 Sigi.The results of the feasibility test in the small group were 86.15% for SMA Negeri 4Sigi, 87.30% for SMA AL-Khairat Kalukubula and 86.73% for SMA Negeri 2 Sigi.These percentages respectively showed that the results of the development ofteaching material supplements received responses. Positive and qualify as eligible tobe used as a supplement of teaching materials.